Analisis Pengaruh Green Marketing dan Perilaku Konsumen Terhadap Keputusan Pembelian Fore Coffee Gwalk Surabaya - Rama, Dimas Aditya; Mubarokah, Mubarokah; Atasa, Dita (Universitas Galuh, 2025)
The Sustainable Development Report reported that there are six Sustainable Development Goals (SDGs) in Indonesia that have increased. One of them is Goal 12 Responsible Consumption and Production. In order to help realize the 12th goal of the SDGs, business owners as parties who do the production activities, implement responsible production activities such as recycling, applying eco-labels, certifying, and so on. This research aims to analyze the effect of green marketing on consumer behavior and analyze the effect of consumer behavior on purchasing decisions at Fore Coffee Gwalk Surabaya. The respondents in this research were 100 Fore Coffee Gwalk Surabaya consumers. The selection of respondents used a purposive sampling method, based on the age criteria of 17 years and over, and had made at least 2 purchases on Fore Coffee products. The analysis technique used Structural Equation Model-Partial Least Square (SEM-PLS) with second order construct using SmartPLS 4 software. The results obtained in this research are green marketing has a positive and significant effect on consumer behavior with a p-value of 0,000 < 0,05 and a t-statistics value of 12,708 > 1,96. Furthermore, consumer behavior also has a positive and significant effect on purchasing decisions with a p-value of 0,000 < 0,05 and a t-statistics value of 12,892 > 1,96.